Multi-functional nanotracers for image-guided stem cell gene therapy. Issue 14 (3rd February 2017) - Park, Ji Sun; Park, Wooram; Kang, A. Young; Larson, Andrew C.; Kim, Dong-Hyun; Park, Keun-Hong
Abstract : A multi-functional stem cell nano-tracer (M-NT) for directing the controlled differentiation and tracking of stem cells is developed through a simple surface modification of gold nanoparticles with a catechol-functionalized polymer. Abstract : Stem cell therapy based on human mesenchymal stem cells (hMSCs) has shown great promise for various disease treatments. However, traditional stem cell-mediated therapy is limited due to their multipotent differentiation ability (uncontrolled spontaneous differentiation) and the difficulty in monitoring cells after implantation in vivo . Here, we report a new multi-functional stem cell nanotracer (M-NT) for directing controlled differentiation through gene delivery, as well as tracking stem cells with dual-modal imaging (optical and CT imaging). The M-NT was prepared through a facile surface modification process of ∼100 nm-sized gold nanoparticles with catechol-functionalized branched polyethylenimine (C-bPEI). The C-bPEI-functionalized M-NT exhibited greatly enhanced long-term colloidal stability in aqueous solution and a capability to complex with plasmid DNA (pDNA; i.e., pEGFP) through electrostatic interaction for gene delivery and transfection to control differentiation. M-NT/pEGFP complexes showed an enhanced transfection efficiency into hMSCs with low cytotoxicity compared with branched polyethylenimine/pDNA complexes. Accordingly, successful in vitro chondrogenic differentiation was achieved in hMSCs treated with M-NT/pSOX9 complexes. Finally, hMSCs transfected with M-NT/pEGFP complexes were transplanted into Balb/c nude mice and successfully visualized through dual-modal optical fluorescence and computed tomography (CT) imaging. We believe that this approach could represent a promising platform for genetic material-mediated direction of differentiation and cell tracking in stem cell therapy.